The Role of Bias Extension Testing to Guide Forming of Non-Crimp Fabrics - Jimenez Martin, Claudia; Maes, Vincent K.; McMahon, Turlough; Kratz, James (Frontiers in Materials, 2022)
The increased production rate targets of the aerospace industry has driven the development of dry fibre processes and biaxial Non-Crimp Fabrics (NCFs). Understanding the forming behaviour of NCFs at scale is key to achieving high quality parts at high rates. Currently, the bias extension test is used to rank materials for forming processes and provide input material data for drape forming models. However, the boundary conditions of this test are often not representative of full-scale forming trials. A direct comparison with wrinkles observed during a forming experiment show that the bias extension test overpredicts wrinkle height. Overall, the bias extension is considered unsuitable on its own for predicting preform quality in an NCF forming process where excess length is generated due to part geometry. If the bias extension is to be used as an NCF material ranking tool, wrinkle height data should be captured alongside force shear data, as shown in this study.